Theories and design principles of multimedia courseware for teachingarabic vocabulary:an analytical and evaluative study - Zainuddin, Nurkhamimi; Sahrir, Muhammad Sabri (International Journal of Technical Reseach and Application, 2015)
This study attempts to analyze and evaluate theories and design principles for design and development of multimedia program for teaching and learning Arabic vocabulary. The researchers mentioned about the research tools, research samples and steps which are related to the design and development process. The study proposes the implementation of social constructivism theory proposed by Vygotsky (1978), theory of second language acquisition by Krashen (1984), theory of multimedia learning by Mayer (2001) and ADDIE instructional model by Dick & Carey (1990). Various subjects matter experts in teaching Arabic as a second language and instructional design (ID) have participated in the study. The outcome from this research will later be used by the researcher in the design and development processes.